The changing role of U.S. corporate research labs - Corcoran, Elizabeth
Elizabeth Corcoran samples the spectrum of redirection, from contracting with business units at GE, Alcoa and elsewhere to provoking "exploratory learning" at Xerox.
With fewer dollars to spend on research, industrial firms are carving out a new role for their central research programs.
Throughout the United States, central research laboratories are facing greater challenges the ever before. As budgets for research laboratories continue to shrink, corporations are demanding more-and faster-tangible results from their laboratories. As a result, research managers are looking for new ways to organize and motivate their programs. Almost every company is pursuing a different strategy. Nevertheless, across the board, managers are trying to pull research into tighter relationship with other divisions of the company. Some worry that a tighter focus on short-term efforts will eventually impair their company's long-term ability to turn out innovations. Others argue that real innovations will come about as research programs become more sensitive to their corporate parent's contemporary problems.
Keywords: Corporate research laboratories--United States